PENGGUNAAN TEKNOLOGI AKUAKULTUR SISTEM BIOFLOK DALAM PROSES PRODUKSI PEMBESARAN IKAN KONSUMSI DI LAHAN SEMPIT - Fadillah Gustaman, Randy; Faisal Mustofa, Romy; Mulyana, Defri; Hamdan, Ahmad (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
The cultivation of tilapia fish presents promising business prospects in the fisheries sector, particularly in Pangandaran Regency. Despite existing efforts to promote tilapia fish cultivation in various villages and sub-districts, the increasing demand for consumption has led to unmet community needs. Limited cultivation land poses a challenge in fulfilling this demand. The adoption of aquaculture technology, specifically the biofloc system, offers a solution to optimize land use and address water conservation concerns. Biofloc technology enables fish farmers to minimize land requirements while enhancing fisheries production efficiency. The key partners involved in the implementation of biofloc technology in tilapia fish cultivation in narrow land areas are the Tidar fisheries business group and the Bina Mandiri fisheries business group, both situated in Pangandaran Regency. The primary issues faced by these fish cultivator groups include traditional cultivation techniques, simplicity and ineffectiveness in tilapia fish production, dependence on manufactured feed due to limited knowledge in feed processing, and the challenge of restricted land availability. By introducing and implementing the biofloc system, these challenges can be effectively addressed, providing a sustainable and efficient solution for tilapia fish cultivation in Pangandaran Regency. This initiative not only meets the increasing market demand for tilapia fish but also promotes environmentally conscious and economically viable aquaculture practices.